Complications related to gastrostomy of patients in home care (Research, Society and Development, 2022)
Objetivos: To analyze the complications of gastrostomies found in patients in home care. Methods: Analytical cross-sectional study, in which a semi-structured form was used in 25 patients. Registered with the Nutrition Management from August to October 2021. The data were processed and attached to a Microsoft Excel spreadsheet. Results: Skin complications were: dermatitis in 8%, hyperemia in 4%, infectious process in 4% and, related to the feeding tube: accidental catheter exit 4%, catheter obstruction 8%; leakage 32%; bleeding 4%. Conclusion: The present study showed that the main complications were related to the adaptation of the catheter used and careful handling, although it is a widely used procedure and considered low risk, gastrostomy still has complications, which can lead to patient hospitalizations.